Chemistry and Applications of Benzimidazole and Its Derivatives 2019
DOI: 10.5772/intechopen.85229
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Profile of Benzimidazoles

Abstract: Benzimidazoles are a class of heterocyclic, aromatic compounds which share a fundamental structural characteristic of six-membered benzene fused to fivemembered imidazole moiety. Molecules having benzimidazole motifs showed promising application in biological and clinical studies. Nowadays it is a moiety of choice which possesses many pharmacological properties extensively explored with a potent inhibitor of various enzymes involved in a wide range of therapeutic uses which are antidiabetic, anticancer, antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 85 publications
(53 reference statements)
0
14
0
1
Order By: Relevance
“…Zhang et al have synthesized a series of 1,2-diarylbenzimidazole derivatives and reported as potential anticancer agents. Among all, the target molecule (12) has been found to show significant cytotoxicity against human cancer cells such as A549, HepG2, HeLa, and MCF-7 cells in the range of GI 50 = 0.71-2.41 μM and also found to show normal cytotoxicity toward normal cells. The apoptosis process by the target compound was confirmed by morphological changes on HepG2 and HeLa-treated cells like cell wall deformation, blebbing, and cell shrinkage, based on apoptosis studies such as mitochondrial membrane potential, annexin V/propidium iodide dual staining assay, and dichlorofluorescein (DCF) fluorescence studies.…”
Section: Tubulin Protein Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al have synthesized a series of 1,2-diarylbenzimidazole derivatives and reported as potential anticancer agents. Among all, the target molecule (12) has been found to show significant cytotoxicity against human cancer cells such as A549, HepG2, HeLa, and MCF-7 cells in the range of GI 50 = 0.71-2.41 μM and also found to show normal cytotoxicity toward normal cells. The apoptosis process by the target compound was confirmed by morphological changes on HepG2 and HeLa-treated cells like cell wall deformation, blebbing, and cell shrinkage, based on apoptosis studies such as mitochondrial membrane potential, annexin V/propidium iodide dual staining assay, and dichlorofluorescein (DCF) fluorescence studies.…”
Section: Tubulin Protein Inhibitorsmentioning
confidence: 99%
“…The benzimidazole derivatives (14) were synthesized under mild conditions with inherently low cost by many researchers using (8), (9), (10), (11), (12), and (13), as reactants (Figure 9). Suheyla et al demonstrated the synthesis of benzimidazoles by condensation of O-phenylene diamine with an appropriate aldehyde (8) in the presence of sodium metabisulfite.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although benzimidazoles are primarily utilized as anthelmintic drugs, they have also presented strong therapeutic application against pathogenic bacteria and fungi [5]. Benzimidazole derivatives are also associated with a variety of types of pharmacological activities such anti-inflammatory [6], antiulcer [7], anti-hypertensive [8] and even possibly anticancer [9].…”
Section: Introductionmentioning
confidence: 99%